Whitney Comorbidity Index to monitor health status for adults with cerebral palsy: validation and thresholds to assist clinical decision making. (7th April 2021) - Whitney, Daniel G; Basu, Tanima
Abstract : Aim: To validate the Whitney Comorbidity Index (WCI), which was recently developed to monitor disease status for adults with cerebral palsy (CP), and to identify WCI scores associated with an increased mortality risk using a representative sample of adults with CP. Method: Data from 2016 to 2018 were used from a random 20% sample from the fee‐for‐service Medicare database for this retrospective cohort study. The WCI was examined as unweighted (WCIunw ) and weighted (WCIw ) among adults at least 18 years old with CP. Cox regression models were developed with mortality as the outcome after adjusting for demographics. A concordance statistic (C‐statistic) of at least 0.70 was considered as showing sufficient validity. The hazard ratio of mortality for each WCI score was estimated. Secondary analyses were performed for subgroups with co‐occurring epilepsy and/or intellectual disabilities. Results: For the entire group ( n =16 728) and subgroups, the WCI showed sufficient validity (C‐statistic 0.73–0.81). For the entire group, the mortality rate was elevated for a score of 1 compared with 0 from the WCIunw (hazard ratio 3.06; 95% confidence interval [CI] 1.52–6.17) and WCIw (hazard ratio 4.08; 95% CI 1.69–9.85), and became larger with each WCI score. Results were similar for the subgroups. Interpretation: The WCI is a valid marker for health/disease status for adults with CP. Several WCI score thresholds were identified to assist in clinical decision making for preventive medicine and intervention implementation. What this paper adds: The Whitney Comorbidity Index (WCI) is valid among 16 728 adults with CP. The WCI is valid for those with co‐occurring epilepsy and/or intellectual disabilities. Thresholds of the WCI score were identified to assist clinical decision making. What this paper adds: The Whitney Comorbidity Index (WCI) is valid among 16 728 adults with CP. The WCI is valid for those with co‐occurring epilepsy and/or intellectual disabilities. Thresholds of the WCI score were identified to assist clinical decision making. This article is commented on by Hilberink on page 767 of this issue. Video Podcast: https://youtu.be/7Uk5gDuq9XA This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Índice de comorbilidad de Whitney para monitorear el estado de salud de los adultos con parálisis cerebral: validación y scores para ayudar a la toma de decisiones clínicas: Objetivo: Validar el Índice de Comorbilidad de Whitney (WCI), que se desarrolló recientemente para monitorear las enfermedades en adultos con parálisis cerebral (PC), e identificar las puntuaciones de WCI asociadas con un mayor riesgo de mortalidad utilizando una muestra representativa de PC de adultos. Método: Para este estudio de cohorte retrospectivo se utilizaron los datos de una muestra randomizada del 20% de la base de datos de pago por servicio de Medicare del 2016 al 2018.El WCI se examinó como no ponderado (WCIunw) y ponderado (WCIw) entre adultos de mas de 18 años con diagnóstico de PC. Los modelos de regresión de Cox se desarrollaron con la mortalidad como resultado después de ajustar por demografía. Se consideró que una estadística de concordancia (estadística C) de al menos 0, 70 mostraba suficiente validez. Se estimó la razón de riesgo de mortalidad para cada puntuación de WCI. Se realizaron análisis secundarios para subgrupos con epilepsia concurrente y / o problemas intelectuales. Resultados: Para todo el grupo (n = 16.728) y subgrupos, el WCI mostró suficiente validez (estadística C 0, 73‐0, 81). Para todo el grupo, la tasa de mortalidad fue elevada para una puntuación de 1 en comparación con 0 de WCIunw (índice de riesgo 3, 06; intervalo de confianza [IC] del 95%: 1, 52–6, 17) y WCIw (índice de riesgo 4, 08; IC del 95%: 1, 69‐9, 85 ), y se hizo más grande con cada puntuación de WCI. Los resultados fueron similares para los subgrupos. Interpretación: El WCI es un marcador válido del estado de salud / enfermedad de los adultos con parálisis cerebral. Se identificaron varios scores de puntuación de WCI para ayudar en la toma de decisiones clínicas para medicina preventiva y para la implementación de intervenciones. Índice de comorbidade de Whitney para monitorar o estado de saúde de adultos com paralisia cerebral: validação e limiares para auxiliar a tomada de decisão clínica: Objetivo: Validar o Índice de Comorbidade de (ICW), que foi recentemente desenvolvido para monitorar o estado da doença de adultos com paralisia cerebral (PC), e identificar pontuações do ICW associadas com maior risco de mortalidade usando uma amostra representativa de adultos com PC. Método: Dados de 2016 s 2018 foram usados a partir de 20% de uma amostra aleatória da base de dados Medicare de cobrança pelo uso para este estudo de coorte retrospectivo. O ICW foi examinado de forma não ponderada (ICWnp) e ponderada (ICWp) entre adultos de pelo menos 18 anos com PC. Modelos de regressão de Cox foram desenvolvidos com a mortalidade sendo o desfecho, após ajustar para demografia. Uma estatística de concordância (estatística C) de pelo menos 0, 70 foi considerada como tendo validade suficiente. A taxa de risco de mortalidade para cada pontuação do ICW foi estimada. Análises secundárias foram realizadas para subgrupos com epilepsia e/ou deficiências intelectuais concorrentes. Resultados: Para o grupo todo ( n =16.728) e subgrupos, o ICW mostrou validade suficiente (estatística C 0, 73–0, 81). Para o grupo inteiro, a taxa de mortalidade foi elevada de um escore de 1 comparada com 0 a partir do ICWnp (taxa de risco 3, 06; intervalo de confiança [IC] a 95% 1, 52–6, 17) e ICWp (taxa de risco 4, 08; IC 95% 1, 69–9, 85), e aumentou com cada pontuação ICW. Os resultados forma similares para os subgrupos. Interpretação: O ICW é um marcador válido para estado de saúde/doença em adultos com PC. Vários limiares de pontuação do ICW foram identificados para ajudar a tomar decisões clínicas na medicina preventiva e implementação de intervenções.